2003
DOI: 10.1086/368071
|View full text |Cite
|
Sign up to set email alerts
|

Abundances of Post–Iron‐Peak Elements in HD 35155: A Symbiotic Star of Spectral Type S

Abstract: We present abundances of Ti, Fe, and Ni as well as 10 post-iron-peak elements in the extrinsic, Galactic S star HD 35155. This star is of interest because it shows many characteristics of symbiotic stars and displays the same pattern of abundance enhancements observed in yellow symbiotic stars. It is clear that HD 35155 is associated with the symbiotic stars and provides an important link between the symbiotic phenomena and chemically peculiar stars. In addition, the abundance ratio of heavy to light s-process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…It is also a binary with one of the longest orbital periods among the families of extrinsic stars (≥54 yr, could be up to 100 yr) (Jorissen et al 2016(Jorissen et al , 2019, but the orbital parameters still have to be confirmed. Our parameters and abundances are in good agreement with those from previous studies (Van Eck et al 2003;Vanture et al 2003;Goswami et al 2016). Here we add the abundances of Gd, Hf, and Os that were not reported earlier.…”
Section: Discussion On Individual Stars and Comparison With Previous supporting
confidence: 92%
“…It is also a binary with one of the longest orbital periods among the families of extrinsic stars (≥54 yr, could be up to 100 yr) (Jorissen et al 2016(Jorissen et al , 2019, but the orbital parameters still have to be confirmed. Our parameters and abundances are in good agreement with those from previous studies (Van Eck et al 2003;Vanture et al 2003;Goswami et al 2016). Here we add the abundances of Gd, Hf, and Os that were not reported earlier.…”
Section: Discussion On Individual Stars and Comparison With Previous supporting
confidence: 92%
“…Only a small number of galactic red symbiotic stars have a cool carbon-rich star as a cool component. Recently, peculiar chemical composition was confirmed for the red symbiotic HD 35155; the star was found to be metal deficient, [Fe/H] = −0.8, and rich in neutron-capture elements, [n/Fe] = + 2 dex on average (Vanture et al 2003). It is not clear why among red symbiotic stars the percent of carbon and s-process rich stars is so low.…”
Section: Introductionmentioning
confidence: 99%
“…Abundances for the neutral species are consistently lower than those of the ionised species. This discrepancy is discussed by many authors for barium stars (Smith 1984;Allen & Barbuy 2006;Smiljanic et al 2007) and S stars (Vanture et al 2003). It is likely caused by NLTE effects affecting the minority species (here the neutral one when T eff ∼ 4500 K).…”
Section: S-processmentioning
confidence: 96%